Behavioral mechanisms underlying trait-mediated survival in a coral reef fish - Rankin, Tauna L.; Cowen, Madeline C.; Kandlikar, Gaurav S.; Shulzitski, Kathryn; Sponaugle, Su (Frontiers in Fish Science, 2024)
Fast growth and large size generally increase survivorship in organisms with indeterminate growth. These traits frequently covary, but where they do not, trade-offs often exist in the behavioral choices of organisms. Juvenile bicolor damselfish Stegastes partitus that settle to coral reefs at larger sizes generally experience enhanced survivorship but have slower juvenile growth rates. We hypothesized that differences in behavior may mediate this trade-off, so to test whether trait-related behaviors or the traits themselves enhance early survival, we combined individual behavioral observations with otolith (ear stone)-based daily growth measurements for juvenile S. partitus in the Florida Keys. Foraging, sheltering, and chasing behaviors of 256 fish were measured during five different months (2008)(2009) and patterns of differential survival were similar to those from a 6-year (2003)(2004)(2005)(2006)(2007)(2008) recruitment time-series. We found a trade-off between sheltering and foraging that significantly explained patterns in size-at-settlement: damselfish that settled at larger sizes spent less time sheltered and more time feeding high in the water column. Juvenile growth rates were unrelated to any of the sheltering-foraging behaviors, but instead were inversely related to adult conspecific density. Damselfish that settled near higher densities of conspecifics were subjected to increased territorial chasing. Chasing intensity interacted with settlement size such that large juveniles who were chased more frequently exhibited slower growth rates, whereas smaller settlers did not experience this energetic cost. Thus, the dominant survival strategy of S. partitus is to settle at a large size and spend more time foraging high in the water column while dodging conspecifics at an Deleted: on reefs Deleted: upper Deleted: selective loss Deleted: We tested three hypotheses Deleted: to identify the behaviors that mediate the trait-related trends in juvenile survival Deleted: .